Fluoride exposure, personal susceptibility and osteoarticular degeneration: Evidence from farmers in the Yellow River Basin of Henan Province - Zichen Feng; Long Sun; Shu Niu; Bin Liu; Ruijie Ba; Guoqing Wang; Qing Sun; Chunxiang Li; Yan Wang; Fangfang Yu; Guoyu Zhou; Yue Ba (Ecotoxicology and Environmental Safety)
Osteoarticular degeneration (OAD) is an important issue. Excessive fluoride can damage osteoarticular health. Besides, personal susceptibility (including genetic factors, physiological characteristics, and lifestyle) also contributes to osteoarticular development significantly. However, little evidence focused on the comprehensive modification of fluoride exposure and personal susceptibility on osteoarticular health. Thus, this study explored the relationships among fluoride exposure, genetic factors, physiological characteristics, lifestyle, and OAD risk, as well as the potential interactions among contributors in 593 adults from a cross-sectional study conducted in 2017. We observed that the OAD (n = 175) risk was increased with increasing urinary fluoride (UF) levels (OR=1.484; 95 %CI: 1.043, 2.111), age (OR=1.065; 95 %CI: 1.033, 1.098), and hip circumference (OR=1.069; 95 %CI: 1.014, 1.127), as well as a poor night sleep quality (OR=1.818; 95 %CI: 1.072, 3.084). More fruit consumption (>350 g/d) was beneficial to OAD prevention (OR=0.102; 95 %CI: 0.012, 0.850). Genetic susceptibility analysis showed that the CG genotype of calcitonin related polypeptide alpha (CALCA) rs1553005 loci was related to higher OAD risk (OR=1.959; 95 %CI: 1.003, 3.825), whereas higher methylation status of GNAS complex locus (GNAS) (OR=0.617; 95 %CI: 0.410, 0.929) and TC genotype of rs7121 loci (OR=0.569; 95 %CI: 0.371, 0.871) showed protective effect on OAD. Additionally, OAD risk was related to the interaction of fluoride-rs1553005 polymorphism-rs7121 polymorphism-GNAS methylation, fluoride-age-fruits, age-fruits, and rs1553005 polymorphism-GNAS methylation-rs7121 polymorphism-age-hip circumference-fruits-UF. Findings suggested that the OAD susceptibility might be modified by the interactions between fluoride and personal susceptibility.